Эстетика. Философия. Критика: в 2 т. (Фридрих Шлегель ; [вступ. ст., сост., пер. с нем. Ю. Н. Попова ; примеч. А. В. Михайлова, Ю. Н. Попова]) - Шлегель Фридрих фон (1983)
Экземпляры: КХ (20110621) / Инвентарный номер: 799636 / Цена: 2.10 / Сис.шифр: 87 / Авт.знак: Ш 68 / ГРНТИ: 02 / ББК: 87.3(4Гем)5